Open-label, multicenter, single-arm phase II DeCOG-study of ipilimumab in pretreated patients with different subtypes of metastatic melanoma. Issue 1 (December 2015) - Zimmer, Lisa; Eigentler, Thomas; Kiecker, Felix; Simon, Jan; Utikal, Jochen; Mohr, Peter; Berking, Carola; Kämpgen, Eckhart; Dippel, Edgar; Stadler, Rudolf; Hauschild, Axel; Fluck, Michael; et al.
Abstract Background Ipilimumab is an approved immunotherapy that has shown an overall survival benefit in patients with cutaneous metastatic melanoma in two phase III trials. As results of registrational trials might not answer all questions regarding safety and efficacy of ipilimumab in patients with advanced melanoma seen in daily clinical practice, the Dermatologic Cooperative Oncology Group conducted a phase II study to assess the efficacy and safety of ipilimumab in patients with different subtypes of metastatic melanoma. Patients and methods We undertook a multicenter phase II study in melanoma patients irrespective of location of the primary melanoma. Here we present data on patients with pretreated metastatic cutaneous, mucosal and occult melanoma who received up to four cycles of ipilimumab administered at a dose of 3 mg/kg in 3 week intervals. Tumor assessments were conducted at baseline, weeks 12, 24, 36 and 48 according to RECIST 1.1 criteria. Adverse events (AEs), including immune-related AEs were graded according to National Cancer Institute Common Toxicity Criteria (CTC) v.4.0. Primary endpoint was the OS rate at 12 months. Results 103 pretreated patients received at least one dose of ipilimumab, including 83 cutaneous, seven mucosal and 13 occult melanomas. 1-year OS rates for cutaneous, mucosal and occult melanoma were 38 %, 14 % and 27 %, respectively. Median OS was 6.8 months (95 % CI 5.3–9.9) for cutaneous, 9.6 months (95 % CI 1.6–11.1) for mucosal, and 9.9 months (lower 95 % CI 2.3, upper 95 % CI non-existent) for occult melanoma. Overall response rates for cutaneous, mucosal and occult melanoma were 16 %, 17 % and 11 %, respectively. Eleven patients had partial response (16 %) and ten patients experienced stable disease (14 %), none achieved a complete response. Treatment-related AEs were observed in 71 patients (69 %), including 20 grade 3–4 events (19 %). No new and unexpected safety findings were noted. Conclusions Ipilimumab is a treatment option for pretreated patients with advanced cutaneous melanoma seen in daily routine. Toxicity was manageable when treated as per protocol-specific guidelines. Trial registration: Clinical Trials.gov NCT01355120